Salting kinetics, salt diffusivities and proximate composition in osmotically dehydrated Pirarucu muscle - Barretto, T. L. [UNESP]; Betiol, L. F. L. [UNESP]; Bellucci, E. R. B. [UNESP]; Telis-Romero, J. [UNESP]; Barretto, A. C. [UNESP]; Carcel, J. A.; Clemente, G.; GarciaPerez, J. V.; Mulet, A.; Rossello, C. (Univ Politecnica Valencia, 2018)
Pirarucu (Arapaima gigas Schinz) farming has been encouraged and, among meat preservation techniques, the salting process is a relatively simple and low-cost method. The objective of this work was to study the sodium chloride diffusion kinetics in Pirarucu during wet salting. Limited volumes of brine (20% w/w) were employed with wet salting assays carried at 3, 4 and 5 brine/muscle ratios, and brine temperatures of 10, 15 and 20 degrees C. The analytical solution of Fick's second law considering one-dimensional diffusion through an infinite slab in contact with a well-stirred solution of limited volume was used to calculate the effective salt diffusion coefficients. Salt diffusivities in muscle were found to be in the range of 2.07 and 8.80 x 10(-10) m(2)/s. The wet salting of Pirarucu is greatly influenced by temperature and by the brine/muscle ratio by volume.
Keywords: Pirarucu; Arapaima gigas Schinz; salt diffusion coefficients; brine